Faktor-Faktor yang Mempengaruhi Customer Satisfaction dan Loyalty Terhadap Coffee Shop di Kota Batam - Novilia, Vera; Mulyana, Elfan Wahyu (Politeknik Negeri Padang, 2022)
The aim of this study is to analyze the effect of product marketing on customer loyalty at a coffee shops in Batam. The Culinary sector in this city is growing rapidly which has many coffee shop businesses, so customer loyalty is one of the important factors in this sector. The sample used in this study comes from customers or the people of Batam City who often visit coffee shops. The approach used on this examine is to apply quantitative methods by distributing questionnaires and this study obtained a total of 325 respondents. The object of research used is some of the leading coffee shops in Batam City. Data analysis was carried out using the Smart PLS 3.2.9 application. The results of this study indicate that product quality, price, service quality, brand image and physical environment have a significant positive effect on customer satisfaction, service quality and brand image have a significant positive effect on customer loyalty through customer satisfaction, customer satisfaction has a significant positive effect on customer loyalty. through customer satisfaction. significant positive effect on customer loyalty.